Avaliação preliminar e confirmatória da contaminação por hidrocarbonetos de petróleo das águas superficiais e subterrâneas no distrito dos mecânicos em Campina Grande-PB - Costa, Cristian José Simões (2015)
This study aimed to conduct a preliminary and confirmatory assessment of environmental impacts to water resources caused by hydrocarbons originating from car repair shops located in the Distrito dos Mecânicos in Campina Grande - PB. This District was built in the 1980s. Thinking about sustainable practices implies assessing the need for a diagnosis of activities that work with petroleum products and a have high power of contamination of surface and groundwater, such as BTEX (benzene, toluene, ethylbenzene and xylenes), HPAs- Polycyclic Aromatic Hydrocarbons, oils and greases. Called micropollutants, aromatics BTEX and PAHs are the most dangerous among the hydrocarbons because they present high toxicity, even at low concentrations. The analysis of BTEX, PAHs, oils and greases in groundwater were carried out at four places in the Distrito dos Mecânicos, selected from the groundwater flow, and the results were compared with the current legislation for the potability standards and contamination of ecosystems. Samples of surface water were analyzed from two collection points in the Riacho das Piabas, located upstream and downstream of the Distrito dos Mecânicos in order to find a possible influence of the activities performed in the space referred to in the water contamination by hydrocarbons. Through in loco visits it was diagnosed that 91% of the establishment do not have a Oil Water Separator - OWS system and the 9% who have do not perform the proper maintenance. The Companhia de Água e Esgotos da Paraíba also has a OWS system that collects all effluent from the Distrito dos Mecânicos, however, periodic maintenance is not done. During the research we found only the BTEX toluene in groundwater and in surface water. Some PAHs were found only in surface water. The levels of oil and grease in the Riacho das Piabas and groundwater were above those recommended by the CONAMA 430/2011 legislation, which indicates the need for further investigation of the study area and for proposing mitigation measures.